(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Structural composition based on diameter and height class distribution of the tree species of Dudhpukuria-Dhopachori Wildlife Sanctuary, Chittagong, Bangladesh was assessed. A total of 183 tree species having ≥ 10 DBH belonging to 125 genera and 48 families was recorded from the study area. Different species were found to dominate in different DBH classes, i.e. Aporosa wallichii (4.06%), Artocarpus chama (1.54%) and Dillenia pentagyna (0.38%) dominated 10 - < 25 cm, 25 - < 40 cm and 40 - < 55 cm DBH, respectively. Swintonia floribunda was found in maximum (7 out of 8) number of DBH classes. Both the percentage of tree individuals (73.18%) and number of species (169) were highest in 10-24.5cm DBH range. Similarly, Dipterocarpus turbinatus (14.5-24.4m and 24.5-34.4m) and Swintonia floribunda (34.5-44.4m and 44.5-54.4m) were dominant in two height ranges each. On the other hand, height range 4.5 - 14.4 m was dominated by Aporosa wallichii (4.36%). Dipterocarpus costatus, Artocarpus chama, Syzygium firmum and Bombax insigne were found in all the height classes. Both the number of tree species and number of individual stems (167 species; 1,684 individuals) were highest in the height range of 4.5-14.4m. The number of species and tree individuals decreased linearly with increasing height. All these indicate that, there was a sustainable natural regeneration and successful recruitment of Aporosa wallichii, Dipterocarpus turbinatus, Lithocarpus acuminata, Grewia nervosa and Artocarpus chama in Dudhpukuria-Dhopachori Wildlife Sanctuary. Dipterocarpus turbinatus was found as dominant species as it constitures maximum (5.56%) percentage of all tree individuals. The findings of the study may be useful for protection, conservation and sustainable management of Dudhpukuria-Dhopachori Wildlife Sanctuary. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(1): 17-30